2010
DOI: 10.1073/pnas.1002459107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-activated glutaminase (GLS2), a p53-inducible regulator of glutamine metabolism and reactive oxygen species

Abstract: We identified a p53 target gene, phosphate-activated mitochondrial glutaminase (GLS2), a key enzyme in conversion of glutamine to glutamate, and thereby a regulator of glutathione (GSH) synthesis and energy production. GLS2 expression is induced in response to DNA damage or oxidative stress in a p53-dependent manner, and p53 associates with the GLS2 promoter. Elevated GLS2 facilitates glutamine metabolism and lowers intracellular reactive oxygen species (ROS) levels, resulting in an overall decrease in DNA oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
492
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 591 publications
(541 citation statements)
references
References 35 publications
21
492
1
7
Order By: Relevance
“…9,10 In particular, GLS2 regulates energy metabolism and antioxidant defense in cancer cells. Indeed our results indicate and confirm that GLS2 is a key player in the regulation of, at least, intracellular ATP levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 In particular, GLS2 regulates energy metabolism and antioxidant defense in cancer cells. Indeed our results indicate and confirm that GLS2 is a key player in the regulation of, at least, intracellular ATP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it regulates ATP levels and the GSH/GSSG ratio in cells. 9,10,37 Hence, we asked whether GLS2 could also exert the same functions in SH-SY5Y cells. First, we overexpressed GLS2 (Fig.…”
Section: Metabolic Function Of Gls2 In Nb Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of p53 augmented GLS2 expression, resulting in enhanced levels of glutamate and α-KG, increased mitochondrial respiration/ATP production, and decreased ROS levels [65]. Moreover, p53 increased GLS2 expression in response to oxidative stress and accumulation of genome damage, reducing tumor formation [67]. p53 activation represses ME1 and ME2, decreasing glutamine metabolism, rather than glucose metabolism, leading to senescence [66].…”
Section: P53mentioning
confidence: 99%
“…A number of studies have shown that glutaminase enzymes play an important role in regulating intracellular levels of ROS. For instance, genetic downregulation of either GLS2 or p53 compromises the GSH-dependent antioxidant system and increases intracellular ROS levels [67]; however, their activation increase GSH levels and decreases ROS levels, leading to cancer survival [65]. On the other hand, glutamine-fueled mitochondrial metabolism generates ROS by OXPHOS activity, leading to cell proliferation and tumorigenesis [57,143].…”
Section: Cellular Redox Balance and Stress Resistancementioning
confidence: 99%